Effectiveness of social stories for children with autism: A comprehensive review. - Aldabas, Rashed (Technology & Disability, 2019)
BACKGROUND: The study primarily focuses on systematically analyzing the effectiveness of using social stories as interventions for inappropriate social behavior in individuals with ASD. OBJECTIVE: This study also reviewed the effectiveness of integration of technology when using social stories. METHODS: Several databases were systematically searched using key words. Exclusion and inclusion criteria were applied to identify appropriate peer-reviewed journal articles for inclusion. Effect size, quality of study, and Gray's criteria were used to assess the efficacy of social stories as interventions for inappropriate behaviors in individuals with ASD. RESULTS: The search yielded 23 peer-reviewed journal articles. The literature indicates that social stories are, in fact, effective in reducing inappropriate social behaviors among such children. A few studies had been about applied social stories with use of technology. However, some researchers have argued that social studies cannot be used alone. CONCLUSIONS: There is a need to ensure that teachers involve themselves fully in the process and include verbal prompts and computer-presented social stories employing multimedia features. According to findings of the literature, further research is needed on the effectiveness of social stories when incorporated with other verbal prompts and multimedia features.